Udział komponentu maglemoskiego w rozwoju kulturowym późnomezolitycznych społeczeństw Pomorza w świetle badań na stanowisku Jastrzębia Góra 4, woj. Gdańsk - Domańska, Lucyna (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The results of the investigations of Jastrzębia Góra, site 4, Gdańsk province, recapitulated in this paper, cast a new light on the problem of cultural changes in Pomerania in the Late Mesolithic. Flint inventories from Pomerania, notably its coastal zone, show distinct links with the Maglemose flint industry. This is pariticularly apparent in the technique of blade production and in the presence of characteristic microliths, notably those with retouched base, of triangles with the retouch of the third side and of narrow rectangle triangles. Moreover, these links are confirmed by characteristic macrolithic and bone tools recorded in certain parts of Pomerania. On this ground, the assemblages of the Jastrzębia Góra type can be assigned to the Maglemose culture and regarded as coeval with its latest phase.